2013
DOI: 10.1128/jvi.01302-12
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus 2 (HSV-2) Prevents Dendritic Cell Maturation, Induces Apoptosis, and Triggers Release of Proinflammatory Cytokines: Potential Links to HSV-HIV Synergy

Abstract: bHerpes simplex virus 2 (HSV-2) may cause frequent recurrences, highlighting its ability to evade host defense. This study tested the hypothesis that HSV-2 interferes with dendritic cell (DC) function as an escape mechanism, which may contribute to enhanced HIV replication in coinfected populations. Immature monocyte-derived human DCs were exposed to live or UV-inactivated HSV-2 or lipopolysaccharide. Little or no increase in the maturation marker CD83 was observed in response to HSV-2 and HSV-2 exposed DCs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
87
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 48 publications
5
87
1
2
Order By: Relevance
“…Luminex analysis confirmed that TNF-a was the major cytokine produced, with minor enhancement of CXCL10 (IP-10) and IL-8. TNF-a production in this setting was consistent with a previous report on HSV-2-infected MDDCs, although we found only low levels of IL-6 (26). Because TNF-a is a soluble trimer, with a total size of 51 kDa, it fits within the identified m.w.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Luminex analysis confirmed that TNF-a was the major cytokine produced, with minor enhancement of CXCL10 (IP-10) and IL-8. TNF-a production in this setting was consistent with a previous report on HSV-2-infected MDDCs, although we found only low levels of IL-6 (26). Because TNF-a is a soluble trimer, with a total size of 51 kDa, it fits within the identified m.w.…”
Section: Discussionsupporting
confidence: 81%
“…Our results showing no effect of HSV-2 superinfection on MDDCs, previously infected with HIV-1 for 4 d to increase HIV-1 DNA, are not contradictory to a previous report (26) where supernatants from HSV-2-exposed MDDCs (containing TNF-a and IL-6) were able to induce HIV-1 replication in the transformed U1 monocytoid cell line where the virus is integrated in every cell. This stimulatory effect of TNF-a on monocytoid cell lines such as U937 and U1 is well-known and operates through the NF-kB sites in the LTR (47).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations